Desarrollo de práctica de automatización a través de un módulo didáctico con el PLC SIMATIC S7-1200 para el arranque de un motor mediante un autotransformador - Chiguano Guamangate, Edwin German (2017)
The present project is oriented towards the implementation of a didactic module with the SIMATIC S7-1200 PLC for the start-up of a motor through an autotransformer to improve the teaching-learning process in the students, in order to be able to practice and complement the theoretical principles acquired, within the Electromechanical Major of the Technical University of Cotopaxi La Maná. The main objective of this project is to develop automation practice through a didactic module with the PLC S7-1200 to start a motor through an autotransformer, in this way facilitate teaching-learning as a fundamental part of the development of a society which is in constant transformation. The implementation of this project will contribute to the advancement of the university and theoretical and practical knowledge of the structure and programming involved in developing a didactic module for starting a motor through an autotransformer, which will allow teachers and students to have a didactic material in his laboratory, for the development as future professionals. It is a contribution as a starting point for the control of motors through an autotransformer with all the current components that will allow to know those in laboratory work and aims to improve the teacher and students knowledge through practice in their professional training.